Comparative pharmaceutico analytical study of Haratala (orpiment) Shodhana (purification) using different Shodhana media - Krupali Shailesh Jani; Prashant Bedarkar; Vinay J Shukla; Biswajyoti Patgiri (Wolters Kluwer Medknow Publications, 2022)
INTRODUCTION: Haratala is Uprasa mentioned since vedic period. Chemically, it is Arsenic trisulfide and also classified under schedule E1 drug. There are methods and medias used for Shodhana of Haratala. In the present study for Shodhana of Haratala, three Shodhana media have been taken, i.e., Triphala Kwatha, Tila Tail, Kanji. AIM: The aim of the study is to standardize pharmaceutical procedure of Haratala Shodhana in different Shodhana media and developing its comparative analytical profile. MATERIALS AND METHODS: Haratala Shodhana is done in different Shodhana Media, i.e., Triphala Kwatha, Tila Taila and Kanji. Total three batches in each Shodhana media were carried out for standardization. RESULTS AND DISCUSSION: Three hour duration was required for 100 g of Shodhana of Haratala average 2l of liquid media used for Shodhana, analytically there was significant difference in all three samples of Haratala was found, Three media were taken, i.e., Triphala Kwatha, Tila Taila, Kanji and there analytical profile will be generated to find the probable variations in before and after Shodhana. CONCLUSION: All three media were used for Shodhana of Haratala because all liquid medias were easily available for Shodhana and all possess different therapeutic utilities. Although there is a significant difference seen analytically after Shodhana, In X-ray diffraction, maximum number of peaks were found in Triphala Kwatha Shodhit Haratala so this could be used as differentiating factor for better comparison between all three Shodhana media.